Implementasi Manajemen Mutu Berbasis Total Quality Management (TQM) dalam Peningkatan Kualitas Pendidikan Teknologi Kejuruan - Ridha Kartini; Nizwardi Jalinus; Ernawati; Henny Yustisia (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the implementation of Total Quality Management (TQM) in improving the quality of Vocational and Technological Education (PTK) in Indonesian vocational high schools. Using a descriptive qualitative approach, the research explores the dynamics of TQM practices through interviews, observations, and document reviews. The findings reveal that quality in vocational education is not driven solely by managerial documentation, but by the consistency of organizational behavior and cultural practices. High-performing schools demonstrate strong instructional leadership, embedded 5S work culture, industry-aligned teacher competencies, and active, sustainable partnerships with industrial stakeholders. In contrast, low-performing schools tend to implement TQM superficially, with incomplete PDCA cycles, inconsistent quality culture, and weak industry engagement. These findings emphasize that the success of TQM implementation relies on four key pillars: visionary leadership, consistent industrial work culture, continuous teacher competence development, and substantive industry collaboration as the primary customer. Therefore, improving vocational education quality requires systemic cultural transformation rather than purely administrative compliance.